Solitary metastases of lower extremity myxoid liposarcoma to breast: A case report and review of literature - Omranipour, Ramesh (Clin Case Rep, 2021)
Solitary breast metastases from myxoid liposarcoma are extremely rare. Resection with negative margins seems as an effective treatment leading to improved survival.